Evaluasi User Experience Gim Defense of The Ancients 2 (DOTA 2) menggunakan Metode Flow Framework - Moh. Laksamana Adhitama; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Defense of the Ancients 2 (DotA 2) is one of the most popular Multiplayer Online Battle Arena (MOBA) games. However, the game design and game play mechanics that have been presented in the game Defense of the Ancients 2 (DotA 2) still have problems, especially in terms of user experience as observed from the flow experience perspective. The following research will exercise a flow framework method which composed of two components, flow antecedents and flow state. Flow antecedents have several dimensions which include playability, clear goals, challenges, feedback and sense of control. The flow state dimension consists of concentration, intrinsic reward, loss of self-consciousness and time distortion. Results of evaluations that have been implemented using the flow framework method on Defense of the Ancients 2 (DotA 2), the quality and user experience on each flow dimension was received. Game Defense of the Ancients 2 (DotA 2) get the value of mean of 4.60 on clear goals, 4.47 mean score on time distortion, 4.35 mean score on loss of self-consciousness, 4.30 mean score on intrinsic reward, 4.07 mean score on feedback, 4.00 mean score on concentration and 3.90 mean score on playability which signify that this game has presented an ease of play. However, with a mean challenge value of 3.50 and a sense of control mean score of 3.77, the game Defense of the Ancients 2 (DotA 2) does not provide a balanced gameplay, where beginners with limited experienced play against solid veteran players or against players which are disruptive and upsetting which resulted a sudden drop on player's motivation and increase on stress level. manually that cost more time. As results of the expert evaluator's recommendations, further improvement need to be done by developing a new system based on flow framework dimension that could measure player's ability, on both new game accounts and old accounts to mitigate the chance of imbalance ability between players on a game session.